A felsőoktatási intézmények szerepvállalása a régió- és városfejlődésben - Keczer, Gabriella (Közép-Európai Közlemények, 2012)
The role of higher education institutions in the development of their regions is inevitable. The so called 3rd role of the universities, that is getting more and more important besides education and research is thoroughly dealt with in literature. The OECD launched a projekct called „Higher Education in Regional and City Development” in 2005, to analyse how the higher education system impacts upon regional and local development. The reviews cover areas with a population of 1-5 million. The reviews investigated the contribution of higher education institutions’ research to regional innovation, the role of teaching and learning in the development of human capital and skills within regions, the contribution of higher education institutions to social, cultural and environmental development for regions and the role of higher education institutions in building regional capacity to act in an increasingly competitive global economy. Until 2010 28 regions have been reviewed. I present the main conclusions of the project, as well as some good practice examples.